Comparison of the effect of two combinations of myo-inositol and D-chiro-inositol in women with polycystic ovary syndrome undergoing ICSI: a randomized controlled trial - Nicolas Mendoza; Maria Paz Diaz-Ropero; Miguel Aragon; Vicente Maldonado; Placido Llaneza; Juan Lorente; Raquel Mendoza-Tesarik; Jose Maldonado-Lobon; Monica Olivares; Juristo Fonolla (Gynecological Endocrinology)
The purpose of this study was to evaluate the effect of two doses of D-chiro-inositol (DCI) in combination with Myo-inositol (MYO) in women with PCOS undergoing ICSI. This was a multicenter controlled, randomized, double-blind parallel group study with two MYO-DCI formulations for 12 weeks. The study group (SG) was administered 550 mg of MYO + 150 mg of DCI twice daily; the control group (CG) was administered 550 mg of MYO + 13.8 mg of DCI twice daily. The participants comprised 60 women with PCOS undergoing ICSI. At baseline, no differences were found between the two groups regarding age, BMI, HOMA-IR or testosterone levels. The pregnancy and live birth rates were significantly higher in the SG than in the CG (65.5 vs. 25.9 and 55.2 vs. 14.8, respectively) [risk ratio (RR) = 0.4; 95%CI (0.2, 0.79); p = .003 and RR = 0.27; 95%CI (0.10, 0.70); p = .002 respectively]. The risk of ovarian hyperstimulation syndrome (OHSS) was lower in the SG (3.44 vs. 18.5%, p = .07). The combination of MYO-DCI at high doses of DCI improves the pregnancy rates and reduces the risk of OHSS in women with PCOS undergoing ICSI.